Study of the Validity of the Constructive System Lad-Ma for the Self-Help Housing of Incremental Housing [Análisis de Vigencia del Sistema Constructivo Lad-Ma Para la Autoconstrucción Asistida de Viviendas Progresivas] - Jimenez-Cavieres, R (CSIC Consejo Superior de Investigaciones Cientificas, 2020)
Since the mid-1980s and until the early ‘90s of the twentieth century, various NGOs working on the housing problem for the most vulnerable segments of society in Chile explored different alternatives to offer practical solutions in a context of political dictatorship and a State with low response capacity. Among the NGOs of the time, «Taller Norte» Technical Assistance Center stands out. This article is part of an investigation that retrieves the technological experience of the LAD-MA construction system design, created to be used in mutual self-help programs. The study analyzes the effect that the economic and political social context of the time had over the system design, seeking to establish the validity of the construction system in the current social economic and political conditions. © 2020 CSIC. Este es un artículo de acceso abierto distribuido bajo los términos de la licencia de uso y distribución Creative Commons Reconocimiento 4.0 Internacional (CC BY 4.0).